2019
DOI: 10.33808/clinexphealthsci.564220
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Associated with Mothers’ Preventive Measures Against Home Accidents: A Descriptive Study from Istanbul, Turkey

Abstract: Objective: One of the most common causes of death among children in Turkey is accidents, and of this, 18-25% caused by home accidents. This study aims to identify the factors associated with safety measures against home accidents, that are taken by mothers who have children between 0-6 years of age. Methods: This descriptive study was conducted among the mothers who admitted to three Family Health Centers in Istanbul, Turkey, in 2017. The data was collected with a questionnaire including "The Scale for Mother'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…The most common type of accident (37.4%) is falling by slipping or tripping over household items. Similarly, in other studies, the most common type of accident was found to be falling (13,(16)(17)(18)(19)(23)(24)(25). When the distribution of home accidents according to the age of the children is examined, the most frequent falls are falling from a height in the 1 age group, falling by tripping or slipping in the 2, 3 and 5 age groups, falling and hitting objects in the 4 age group, and cuts in the 6 age group.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The most common type of accident (37.4%) is falling by slipping or tripping over household items. Similarly, in other studies, the most common type of accident was found to be falling (13,(16)(17)(18)(19)(23)(24)(25). When the distribution of home accidents according to the age of the children is examined, the most frequent falls are falling from a height in the 1 age group, falling by tripping or slipping in the 2, 3 and 5 age groups, falling and hitting objects in the 4 age group, and cuts in the 6 age group.…”
Section: Discussionsupporting
confidence: 68%
“…This shows that the awareness of the mothers as a result of the experiences they have with their children is more important than the age and number of children. In other studies, no statistically significant difference was found between family type, income status, type of house, number of children living in the house, number of individuals living in the house, number of rooms in the house, child age groups, and mothers' total mean scores (17,25).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…6 Preventing home injuries is an essential part of the child health care program, and one of the main responsibilities of parents and caregivers. 7 Parents' interventions can significantly decrease the possibility of unintentional injuries among children. 8 Using educational programs promotes mothers' awareness, attitude, and practices regarding injury prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing home injuries is an essential part of child care program and one of the main responsibilities of parents and caregivers (6). Parenting interventions can significantly decrease the possibility of unintentional injuries among children (7).…”
Section: Introductionmentioning
confidence: 99%